Analysis of Economic Improvement through Sharia Economic Resource Development Towards Sustainable Prosperity in Indonesia - Adibah, Alda Naila; Zakariya, Achmad (Journal of Finance, Economics and Business, 2024)
This article discusses an analysis of economic improvement through the development of sharia economic resources to achieve sustainable prosperity in Indonesia. With the background of sharia economics as a system that emphasizes common interests and fair distribution of wealth, the article outlines the role of fatwas as a form of regulation in the development of sharia economics in Indonesia. Even though Indonesia has a majority Muslim population, the growth of the sharia banking industry is faced with challenges of sharia banking literacy and inclusion. Using the library research research method, the article presents the results of an analysis of sharia economic resource development by highlighting the existence of sharia banks and the role of financial institutions in improving community welfare. The development of sharia economic resources also includes the growth of the sharia economic sector in the era of globalization, with a focus on sharia financial institutions such as banks, insurance, pawnshops, capital markets, mutual funds, and Baitul Mal wat Tamwil (BMT). Next, the article discusses the challenges and opportunities faced in sharia economic development, especially related to sharia banking literacy and inclusion. In the context of the digital era, the adaptation of Islamic banks to changes and the use of technology is crucial to seize opportunities for product development and quality human resources. The article highlights the importance of data security, cost efficiency, and the role of technology in facing challenges amidst the ever-growing dynamics of sharia banking